An evaluation of adverse drug reactions and outcomes attributed to kratom in the US Food and Drug Administration Adverse Event Reporting System from January 2004 through September 2021 - Xiaotong Li; Patrick Ndungu; Sanya B. Taneja; Maryann R. Chapin; Susan B. Egbert; Krishi Akenapalli; Mary F. Paine; Sandra L. Kane‐Gill; Richard D. Boyce (Wiley, 2023)
Abstract Kratom is a widely used Asian botanical that has gained popularity in the United States due to a perception that it can treat pain, anxiety, and opioid withdrawal symptoms. The American Kratom Association estimates 10-16 million people use kratom. Kratom‐associated adverse drug reactions (ADRs) continue to be reported and raise concerns about the safety profile of kratom. However, studies are lacking that describe the overall pattern of kratom‐associated adverse events and quantify the association between kratom and adverse events. ADRs reported to the US Food and Drug Administration Adverse Event Reporting System from January 2004 through September 2021 were used to address these knowledge gaps. Descriptive analysis was conducted to analyze kratom‐related adverse reactions. Conservative pharmacovigilance signals based on observed‐to‐expected ratios with shrinkage were estimated by comparing kratom to all other natural products and drugs. Based on 489 deduplicated kratom‐related ADR reports, users were young (mean age 35.5 years), and more often male (67.5%) than female patients (23.5%). Cases were predominantly reported since 2018 (94.2%). Fifty‐two disproportionate reporting signals in 17 system‐organ‐class categories were generated. The observed/reported number of kratom‐related accidental death reports was 63‐fold greater than expected. There were eight strong signals related to addiction or drug withdrawal. An excess proportion of ADR reports were about kratom‐related drug complaints, toxicity to various agents, and seizures. Although further research is needed to assess the safety of kratom, clinicians and consumers should be aware that real‐world evidence points to potential safety threats.